2015
DOI: 10.1021/acs.jmedchem.5b00951
|View full text |Cite
|
Sign up to set email alerts
|

Quaternary Indolizidine and Indolizidone Iminosugars as Potential Immunostimulating and Glycosidase Inhibitory Agents: Synthesis, Conformational Analysis, Biological Activity, and Molecular Docking Study

Abstract: New quaternary indolizidine iminosugars, with hydroxymethyl group at the ring junction, namely, C-8a-hydroxymethyl-1-deoxycastanospermine congeners 1a, 2a, 3a and their 3-oxo analogs 1b, 2b, and 3b were synthesized by using intramolecular reductive aminocyclization/lactamization of d-mannose/D-glucose derived C5-γ-azido esters as a key step wherein both the rings of the indolizidine skeleton were built up in one pot following the cascade reaction pathway. The conformations ((5)C8 or (8)C5) of 1-3 were assigned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…workers reported α-geminal dihydroxymethyl substituted piperidines. [112] Fustero, Aceña and co-workers used a carbon trifluoride rearrangement to an iminium ion in a quaternary center forming step and applied the methodology in iminosugar synthesis.…”
Section: P E R S O N a L A C C O U N T T H E C H E M I C A L R E C O R Dmentioning
confidence: 99%
“…workers reported α-geminal dihydroxymethyl substituted piperidines. [112] Fustero, Aceña and co-workers used a carbon trifluoride rearrangement to an iminium ion in a quaternary center forming step and applied the methodology in iminosugar synthesis.…”
Section: P E R S O N a L A C C O U N T T H E C H E M I C A L R E C O R Dmentioning
confidence: 99%
“…In their study, these compounds showed potent inhibitory activity against various glycosidase enzymes having K i and IC 50 values in the micromolar/nanomolar concentration range. 17 Sampath Kumar and co-workers screened a focused library of benzyloxyalkyl-substituted 1,2,3-triazolyl α-GalCer analogues for immunomodulatory activity. 18 Bharate and co-workers discovered 7-(prolinol-N-yl)-2-phenylamino-thiazolo [5,4-d]pyrimidines as a novel chemotype of non-nucleoside partial agonists of the A2A adenosine receptor.…”
Section: Editorial: Medicinal Chemistry Research In Indiamentioning
confidence: 99%
“…One recent example by Py and co‐workers, involved synthesis of aziridinyl imino sugars via nitrone‐alkyne cycloaddition and subsequent Baldwin rearrangement . Earlier, Dhavale and co‐workers reported α‐geminal dihydroxymethyl‐substituted piperidines by a route which included a variant of the Corey–Link reaction via suitably oxidized furanoses . Fustero, Aceña and co‐workers prepared chiral lactones using a carbon trifluoride rearrangement to an iminium ion in the quaternary center forming step and applied the methodology in imino sugar synthesis …”
Section: Introductionmentioning
confidence: 99%